ТЕРМИНЛЕРДИ ТИЛЛИК АСПЕКТТЕ ИЗЕРТЛЕЎ МӘСЕЛЕСИ - Карибаева, А.У. (FAN va JAMIYAT, 2024)
The article analyzes the study of terms in the linguistic aspect, systematization and analysis of formation, effective methods and methods of forming terms in the modern Kazakh language.